PENDIDIKAN FISIKA DAN KETERKAITANNYA DENGAN LABORATORIUM - Azhar Azhar (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2008)
Physics represent process and product about natural study. Physics Education representcreativity development and is intellectual of student. Execution Physics education of told effectiveif student can obtain get skill and knowledge think needed to reach final performansi whichwanted. Efficacy learn physics do not only determined by at cognate ability, afektif, andpsikomotor, but more than that also knowledge about erudite process, individual skill, and physicsknowledge which need to be conceptually mastered. Therefore in physics study have its have tosupporting laboratory, so that student get the physics more aktual and do not drag on student.Key words : Physics education, physics knowledge, conceptually, laboratory